Institution Communication management tools for the organization of the Cerebral Vascular Accident (CVA) care line (Research, Society and Development, 2025)
Cerebrovascular accident (CVA) is one of the main causes of morbidity and mortality in the world, requiring quick and well-structured responses to address it. Objective: to develop and implement communication management tools to optimize the organization of the stroke care line, aiming at improving clinical outcomes, care efficiency, cost reduction, and strengthening interdisciplinary work. Methodology: the study was conducted using exploratory methods, supported by the assumptions of cross-sectional action research, with a quantitative and qualitative approach, analyzing indicators such as response time in care, clinical outcomes, and quality of interdisciplinary communication. Results: the centralization of information in the application will minimize errors related to communication and facilitate clinical decision-making, aligning with national and international patient safety guidelines. Conclusion: the integration promoted by the application aims to improve the quality of interdisciplinary work, contributing to the continuity of care, from the acute phase to rehabilitation.